Głęboka dystrakcja jako zasada semiotyczna w społecznie zaangażowanych grach przeglądarkowych o tematyce politycznej - Babecki, Miłosz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This study presents an analysis of the pattern of communication between developers of socially engaged browser games with political themes and their players. This pattern involves a multilevel disruption of the message carried by the game medium and its construct. The solution is being used by the creators to show and comment on the causes and manifestations of negative processes related to politicians and politics and also having a negative impact on social, economic and cultural issues in their countries. In the course of the analysis, its author considers 141 browser games, originating from 23 countries around the world. Their creators made them between 2000 and 2022, and placed them in publicly accessible portals, offering access to online games via a web browser.